Generating Bessel Beams with an Elastomeric Replica of a Weevil Carapace - Ramos, Paz Victoria T. (Archīum Ateneo, 2024)
We generate a zero-order Bessel beam with a laser beam focused onto an elastomeric replica of a weevil carapace scale. Carapace surface structures are imprinted on an elastomeric cast via soft lithography. The output Bessel beam exhibits the expected properties of non-diffraction over a propagation range of 30 cm. The width of the central spot at a propagation distance of 25 cm is 296:8 μm, corresponding to a replicated weevil scale with a diameter of 64.3 μm acting as an annular slit. Self-healing of the beam after encountering a wire obstruction is also observed.